Multisystemic Complications and Rapid Decline in Anti‐MDA‐5 Positive Amyopathic Dermatomyositis: A Case Study - Hem Prajapati; Yesha R. Chauhan; Sahaj Y. Patel; Ajay C. Parmar; Tasin Mohammedyakub Shaikhjiwala (Clinical Case Reports)
ABSTRACT Anti‐MDA‐5 positive amyopathic dermatomyositis (CADM) can lead to rapid multisystemic complications, including severe interstitial lung disease (ILD). This case, involving a 60‐year‐old female with worsening skin lesions and ILD, demonstrates the disease's aggressive nature, highlighting the need for early diagnosis and comprehensive immunosuppressive therapy to improve patient outcomes.